Integrated project delivery (IPD) in Malaysian construction industry dealing with waste issue - Abdul Rahim, Syukran; Abdul Nifa, Faizatul Akmar; Mohd Nawi, Mohd Nasrun (AENSI Journals, 2015)
The Malaysian construction industry is a significant contributor to the nation's economy, due to rapid development of infrastructures in Malaysia. However, there are still issues with the aspects of procurement and management within the construction industry in Malaysia, that can be improved to be more efficient and more cost saving.At present, the wastage from construction industry is drowning billions of Ringgit into nothing.This paper will look into the physical and non physical wastage from construction projects. The waste that can be avoided with a good management system such as value management (VM), concurrent engineering (CE) and integrated project delivery (IPD) will also be discussed in this paper.Accordingly, this paper highlights how IPD can be a platform for cost saving and reducing the waste in the construction industry, by considering each the characteristic of IPD as a system within the construction process.This paper concludes with highlighting how IPD principles can be adapted in current construction processes to reduce waste and improve the project team efficiency.